2016
DOI: 10.1161/strokeaha.116.012700
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Stroke Following Percutaneous Coronary Intervention by Indication

Abstract: Background and Purpose-Stroke after percutaneous coronary intervention (PCI) is a serious complication, but its determinants and outcomes after PCI in different clinical settings are poorly documented. Methods-The British Cardiovascular Intervention Society (BCIS) database was used to study 560 439 patients who underwent PCI in England and Wales between 2006 and 2013. We examined procedural-type specific determinants of ischemic and hemorrhagic stroke and the likelihood of subsequent 30-day mortality and in-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
1
11
0
3
Order By: Relevance
“…Multiple studies have demonstrated that stroke occurrence post‐PCI increased subsequent mortality by a considerable margin . The finding in our analysis is consistent with these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have demonstrated that stroke occurrence post‐PCI increased subsequent mortality by a considerable margin . The finding in our analysis is consistent with these studies.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, CHA 2 DS 2 -VASc score was significantly associated with the risk of post-procedural ischemic stroke following PCI. Although the predictive value of CHA 2 DS 2 -VASc score in predicting ischemic stroke following PCI is less established, the individual components of the CHA 2 DS 2 -VASc score have been demonstrated to represent significant risk factors for post-procedural ischemic stroke 27 , 28 . For example, an analysis of 426,046 patients undergoing PCI in England and Wales between 2007 and 2012 in the British Cardiovascular Intervention Society (BCIS) database demonstrated that age, female gender, a history of stroke were significant predictors of post-procedural ischemic stroke/TIA, and ischemic stroke was independently associated with both 30-day mortality and in-hospital major adverse cardiovascular events (a composite of in-hospital mortality, myocardial infarction or reinfarction, and revascularization) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…We can observe that cardiac thrombi are often created in the ventricular portion that is dikinetic after previous cardiac ischemia. Additionally, the standard gold treatment for the acute cardiac ischemia, the percutaneous coronary intervention, has an intrinsic risk for ischemic stroke of ≈0.1% with the modern techniques [ 136 ]. Nowadays, better methods of reperfusion, the knowledge of the relevance of the antiplatelet therapy, and the optimized medical therapy for the secondary prevention have reduced the risk of cerebral ischemia compared to the past [ 137 ].…”
Section: Cardioembolic Strokementioning
confidence: 99%